JORNALISMO, DIVULGAÇÃO CIENTÍFICA E EDUCAÇÃO: das diferentes nuanças e estratégias ao contexto escolar - Sousa, Carlos Erick Brito de (2009)
We search understand in this work how are processed the relations between journalism, scientific divulgation and education, in their different nuances and strategies whose echos and reflections are extended to school context. We have like general objective to demonstrate the perspectives, possibilities and contributions in these relations. We still aim: to analyze the different strategies of scientific divulgation, perceiving how these relations are manifested in the discourses and practices of the school context. Like proceeding, we adopt the qualitative research (bibliographic, documental and empirical), having like instruments: the analysis of scientific divulgation texts (journalistic reporting and divulgation articles); the fulfillment of semi-structured interviews with teachers and students and the proposition of drawings to the students of the Rede Pública Municipal de Educação de São Luís - MA. To analyze the data generated by the research, we proceeding with orientations of discourse analysis. The complexity of these relations has requisitioned interdisciplinary reference, enveloping the theoretical and methodological contributions from the researches of Communication, Education and Scientific Divulgation. In this way, we search support in Bourdieu (1997, 1997a), Rodrigues (2001) and Traquina (1993a, 2005) to treat of the discussions about journalistic field. To approach the scientific divulgation in their different spaces and activities as well as their approximations with the field of education, we search sustenance in Gomes (2001), Oliveira (2002), Massarani and Moreira (2002a) and Zamboni (2001). And to analyze the different nuances, strategies and representations in the school context we have like base: Andrade and Martins (2006), Bakhtin (2000), Gouvêa (2005), Orlandi (2007) and Studart (2008). We ascertain that the discourse of scientific divulgation assumes a heterogeneous form in their different contexts and vehicles of divulgation, reconfiguring itself conform the realities where appears, thus, in the educational context, it is important search ways to interpret these productions and the reflections that can accrue of this use like a stimulus to learning. We observe the presence of mediatic products in the school compass, between these the magazines of scientific divulgation inside of the practices fulfilled in space of classroom. We emphasize the importance of a social environment that can favor the readers formation, because the children get articulate others senses to the texts read, stimulating their cognitive development and creative capacities. In this way, it is necessary to promote the insertion of different activities of scientific divulgation (and with more frequency) in the school context, their contributions can offer an enrichment (in the sense of problematization) of the matters worked in the school space confronting them and/or complementing them.